Bach1 modulates AKT3 transcription to participate in hyperglycaemia‐mediated EndMT in vascular endothelial cells. (26th March 2023) - Meng, Zhipeng; Shen, Wenchao; Yu, Lang; Tong, Fei; He, Huanzhong; Hu, Yonghe; Wu, Weifei; Liu, Jing
Abstract: Hyperglycaemia‐mediated endothelial‐to‐mesenchymal transition (EndMT) is involved in the occurrence and progression of cardiovascular complications in diabetic patients. Previous studies reported that AKT serine/threonine kinase 3 (AKT3) and Bric‐a‐brac/Tramtrack/Broad (BTB) and cap'n'collar (CNC) homology 1 (bach1) participates in endothelial injury and epithelial‐to‐mesenchymal transition. In the present study, we proposed that bach1 regulates AKT3 transcription, thus involved in hyperglycaemia‐mediated EndMT in vascular endothelium. Our results indicated that hyperglycaemia/high glucose increased AKT3 expression and induced EndMT in aorta of diabetic rats and hyperglycaemic human umbilical vein endothelial cells (HUVECs). Moreover, inhibition of AKT3 expression reversed high glucose‐mediated EndMT in HUVECs. Further, hyperglycaemia/high glucose augmented bach1 expression in aorta of diabetic rats and hyperglycaemic HUVECs. Furthermore, si‐bach1 countered high glucose‐induced AKT3 expression and EndMT in HUVECs. In addition, the effect of bach1 overexpression is similar to that of high glucose treatment, which was reversed by si‐AKT3. ChIP assays found bach1 enriched in the promoter region of AKT3. Bach1 overexpression augmented AKT3 promoter activity, which lost after specific binding site mutation. Bach1 was involved in hyperglycaemia‐induced EndMT via modulation of AKT3 transcription.